2017
DOI: 10.1074/jbc.m117.785592
|View full text |Cite
|
Sign up to set email alerts
|

An HNF4α–microRNA-194/192 signaling axis maintains hepatic cell function

Abstract: Hepatocyte nuclear factor 4α (HNF4α) controls the expression of liver-specific protein-coding genes. However, some microRNAs are also modulated by HNF4α, and it is not known whether they are direct targets of HNF4α and whether they influence hepatic function. In this study, we found that HNF4α regulates microRNAs, indicated by marked down-regulation of miR-194 and miR-192 (miR-194/192) in liver-specific -null () mice. Transactivation of the shared miR-194/192 promoter was dependent on HNF4α expression, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 57 publications
1
61
0
Order By: Relevance
“…Accordingly, miR-194 abundance was reduced and inversely correlated with that of PTBP1 in HCC tissues and in GEO and TCGA cohorts. This is consistent with earlier studies demonstrating that miR-194 functions as a tumor suppressor in HCC [45][46][47][48][49]. These studies revealed that the expression of miR-194 is reduced in HCC tissues and that these HCC show aggressive clinicopathological phenotypes with high proliferation, increased tumor size and metastasis, poor prognosis, and reduced overall and disease-free survival, suggesting that miR-194 is a tumor suppressor and a prognostic factor for HCC.…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, miR-194 abundance was reduced and inversely correlated with that of PTBP1 in HCC tissues and in GEO and TCGA cohorts. This is consistent with earlier studies demonstrating that miR-194 functions as a tumor suppressor in HCC [45][46][47][48][49]. These studies revealed that the expression of miR-194 is reduced in HCC tissues and that these HCC show aggressive clinicopathological phenotypes with high proliferation, increased tumor size and metastasis, poor prognosis, and reduced overall and disease-free survival, suggesting that miR-194 is a tumor suppressor and a prognostic factor for HCC.…”
Section: Discussionsupporting
confidence: 92%
“…The MIR192 / 194–2 genes are involved in the pathway of cancer. Hepatocyte nuclear factor 4α regulates expression of MIR192 and MIR194–2 . NUPR1 is induced by stress or mitochondrial dysfunction, and plays an important role in the growth and migration of human tumor cells .…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocyte nuclear factor 4 alpha (HNF4α) is considered the master regulator of hepatocyte differentiation because of its essential role in embryonic development, stabilizing the hepatic transcription factor network and maintaining hepatocyte function . HNF4α regulates genes involved in xenobiotic metabolism, carbohydrate metabolism, fatty acid metabolism, bile acid synthesis, blood coagulation, and ureagenesis .…”
mentioning
confidence: 99%
“…H epatocyte nuclear factor 4 alpha (HNF4α) is considered the master regulator of hepatocyte differentiation because of its essential role in embryonic development, (1,2) stabilizing the hepatic transcription factor network (3) and maintaining hepatocyte function. (4) HNF4α regulates genes involved in xenobiotic metabolism, carbohydrate metabolism, fatty acid metabolism, bile acid synthesis, blood coagulation, and ureagenesis. (5) Expression of HNF4α induces hepatocyte-like characteristics in induced pluripotent stem cells, (6) and forced expression of HNF4α induces differentiation and decrease cancer Abbreviations: AAV8, adeno-associated virus serotype 8; AKR1B7, aldo-keto reductase family 1, member B7; AKT, protein kinase A; ALAS2, 5′-aminolevulinate synthase 2; APOA2, apolipoprotein A2; APOB, apolipoprotein B; AUC, area under the curve; CCND1, cyclin D1; CDK4, cyclin-dependent kinase 4; CDKN3, cyclin-dependent kinase inhibitor 3; CLDN1, claudin 1; CYP2C37, cytochrome P450, family 2. subfamily C, polypeptide 37; DIO1, iodothyronine deiodinase 1; Dox, doxycycline; ECT2, epithelial cell transforming 2; EGF, epidermal growth factor; EGFR, epidermal growth factor receptor; EGR1, early growth response 1; EP300, E1A-binding protein P300; ERK1/2, extracellular signal-regulated kinases 1 and 2; Esrra, estrogen receptor; F12, coagulation factor XII; GSK-3, glycogen synthase kinase 3 beta; HCCs, hepatocellular carcinomas; HMGB1, high mobility group box 1; HNF1A, hepatocyte nuclear factor 1 homeobox A; HNF4, hepatocyte nuclear factor 4 alpha; HNF4A, hepatocyte nuclear factor 4 alpha; IPA, Ingenuity Pathway Analysis; IRF, interferon regulatory factor; KO, knockout; LR, liver regeneration; c-MET, MET proto-oncogene; MYC, MYC proto-oncogene, BHLH transcription factor; NFIX, nuclear factor I X-type; PCNA, proliferating cell nuclear antigen; PH, partial hepatectomy; PP2, pyrazolo pyrimidine type 2; PPARGC1A (PGC1A), peroxisome proliferator-activated receptor gamma coactivator 1-alpha; PTMs, posttranslational modifications; RNA-Seq, RNA sequencing; SMAD, small mothers against decapentaplegic; SNAI2, snail family transcriptional repressor 2; SREBF, sterol-regulatory element-binding transcription factor; TGF, transforming growth factor beta; UGT2B1, UDP glucuronosyltransferase 2 family, polypeptide B1; WT, wild type.…”
mentioning
confidence: 99%